Who was Lucille Ball? - Pollack, Pam; Belviso, Meg; Copeland, Gregory (New York, New York : Grosset & Dunlap, an imprint of Penguin Random House, 2017)
Presents the life of the comic actress, discussing her childhood, marriage to and divorce from Desi Arnaz, and her career on the successful television hit series "I Love Lucy."
Who was Lucille Ball? -- Lucyball -- Ain't meant for show business -- Queen of the Bs -- Mr. and Mrs. Arnaz -- America loves Lucy -- Little Ricky -- Back to Broadway -- Changing times -- Queen of comedy -- Timelines.
Includes bibliographical references (pages 106-107).
Keywords: Ball, Lucille, -- 1911-1989 -- Juvenile literature; Ball, Lucille, -- 1911-1989.; Ball, Lucille, -- 1911-1989.; Actresses -- United States -- Biography -- Juvenile literature; Comedians -- United States -- Biography -- Juvenile literature; Entertainers -- United States -- Biography -- Juvenile literature; Entertainers; Women -- Biography; JUVENILE NONFICTION / Biography & Autobiography / Performing Arts; JUVENILE NONFICTION / Biography & Autobiography / Women; JUVENILE NONFICTION / Humor; Actresses; Comedians; Entertainers; Entertainers -- United States -- Biography; Actresses -- United States -- Biography; Comedians -- United States -- Biography; United States; United States; Biographies; Biography; Juvenile works; Biographies